2020
DOI: 10.7554/elife.55954
|View full text |Cite
|
Sign up to set email alerts
|

Near-atomic structures of the BBSome reveal the basis for BBSome activation and binding to GPCR cargoes

Abstract: Dynamic trafficking of G protein-coupled receptors (GPCRs) out of cilia is mediated by the BBSome. In concert with its membrane recruitment factor, the small GTPase ARL6/BBS3, the BBSome ferries GPCRs across the transition zone, a diffusion barrier at the base of cilia. Here, we present the near-atomic structures of the BBSome by itself and in complex with ARL6GTP, and we describe the changes in BBSome conformation induced by ARL6GTP binding. Modeling the interactions of the BBSome with membranes and the GPCR … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 78 publications
3
44
0
Order By: Relevance
“…High-resolution structures are available for several IFT sub-complexes [ 106 110 ] and lower resolution structures of complete IFT trains were determined in situ by cryo-ET [ 111 ]. Furthermore, several recent structural cryo-EM studies of mammalian BBSome complexes were recently published [ 112 115 ]. The IFT and BBSome complexes were extensively reviewed previously and will not be further covered here [ 105 , 116 ].…”
Section: Intraflagellar Transport On Doublet Microtubulesmentioning
confidence: 99%
“…High-resolution structures are available for several IFT sub-complexes [ 106 110 ] and lower resolution structures of complete IFT trains were determined in situ by cryo-ET [ 111 ]. Furthermore, several recent structural cryo-EM studies of mammalian BBSome complexes were recently published [ 112 115 ]. The IFT and BBSome complexes were extensively reviewed previously and will not be further covered here [ 105 , 116 ].…”
Section: Intraflagellar Transport On Doublet Microtubulesmentioning
confidence: 99%
“…In contrast, purified IFT172, an IFT-B component that is also homologous to COPI and ' like WDR35, can not only assemble on liposomes with high affinity but can also bud 50nm vesicles consistent with coatomer sized products (Wang et al, 2018). Together this evolutionary conservation of the BB-Some with coatomer proteins (Jékely and Arendt, 2006;van Dam et al, 2013), interaction with in vitro membranes in presence of ARF like GTPase ARL-6, interaction with phospholipids (Jin et al, 2010;Nachury et al, 2007) and recent cryoEM structures of the complex (Chou et al, 2019;Klink et al, 2020;Singh et al, 2020;Yang et al, 2020) suggest the BBSome may be working as an adaptor for IFT-A mediated cage formation, similar to other coat adaptors for clathrin (i.e.AP1/AP2) or COP (i.e. -, -, -, and -COP for COPI).…”
Section: Discussionmentioning
confidence: 90%
“…A recent study has shown that the CTS within the IC3 loop of SSTR3 provides strong binding to a recombinant BBSome core complex, but that the IC3 loop of 5-HT-6 receptor, which is similar to that of rhodopsin, provided only weak interaction (Klink et al, 2017 ). This weak interaction, as well as the presence of an FR motif in rhodopsin helix 8, which also has weak affinity to the BBSome (Klink et al, 2017 ; Yang et al, 2020 ), may support the low presence of rhodopsin in primary cilia (Trivedi and Williams, 2010 ; Trivedi et al, 2012 ; Wang et al, 2012 ; Geneva et al, 2017 ; Chadha et al, 2019 ).…”
Section: The Bbsome In Photoreceptorsmentioning
confidence: 99%